"A" is the aim? - Kamila Danilowicz-Gösele (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
This paper analyzes professors' effect from a fundamental first-year course in Economics on students' later performance in follow-on courses with a special attention given to the problem of self-selection bias of students toward certain professors. Based on an extensive dataset consisting of administrative data on more than 2, 900 students from the university of Göttingen, an instrumental variable (IV) strategy is used. The obtained results indicate that professors have powerful effects on students' achievement. However, the sign of this effect is ambiguous, and depends on the mathematical rigor of the course and the examination style.
Keywords: I23; I21; I28; 330; university; education; grade inflation